Denture stomatitis and its management: Denture stomatitis dan penatalaksanaannya - Andi Mirna Nasliah; Edy Machmud (Makassar Dental Journal PDGI Makassar, 2024)
Dentures worn by elderly become loose over time, and can cause denture stomatitis, because there are many colonies of Can-dida albicans spp in the oral cavity, which can cause inflammation. The purpose of this literature review is to compare the ana-lytical methods used and discuss the best treatment method for denture stomatitis cases. A literature search was conducted using Elsavier, Pubmed, Semantic Scholar and other sources with the keywords Candida albicans and denture stomatitis. It was found that there are many causes of denture stomatitis, most commonly due to Candida spp. It was concluded that denture stomatitis can be cured by eliminating predisposing factors, soaking in antiseptic solutions and the use of antifungal drugs.